Network analysis of the relationship between error orientation, self-efficacy, and innovative behavior in nurses - Guiyue Ma; Xiaoqin Ma (Scientific Reports)
Abstract Nurses’ innovative behavior is essential in the evolving healthcare landscape. This study, guided by the theory of challenge and threat, aims to explore the relationships between nurses’ error orientation, self-efficacy, and innovative behavior through network analysis. A cross-sectional study design was utilized, involving 706 participants from 23 hospitals across six provinces and one municipality directly under the jurisdiction of the central government in China. Participants completed an error orientation questionnaire, the general self-efficacy scale, and the nurse innovative behavior scale online. Data analysis was conducted using SPSS and R, with the network structure, symptom centrality, and outcome robustness evaluated through the qgraph and bootnet packages in R. In the network structure encompassing error orientation, self-efficacy, and innovative behavior, self-efficacy demonstrated the strongest closeness and betweenness centrality, followed by innovative behavior and error orientation. Among these variables, self-efficacy was most closely associated with innovative behavior. Within the dimensions of error orientation, the strongest connection with self-efficacy was found in the aspect of thinking about errors, followed by error communication, error competence, learning from errors, and error risk taking. This network analysis identified self-efficacy as the most influential factor in promoting nurses’ innovative behavior. The findings suggest that clinical educators and hospital managers should focus on enhancing nurses’ self-efficacy to foster their innovative behavior and effectively manage error orientation.